TINJAUAN HUKUM POSITIF DAN FIKIH SIYASAH TERHADAP KEWENANGAN PENJABAT SEMENTARA KEPALA DAERAH DI INDONESIA - Ababil, Muhammad Thoriq; Sukti, Surya (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2024)
This research is motivated by a crucial problem in the government system, namely how weak the Acting Regional Heads are. Acting regional heads should be leaders who are able to bring about positive change, not just puppets who are bound by the rules. Therefore, this study focuses on the provisions of positive legal review and siyasah jurisprudence regarding restrictions on the leadership authority of acting regional heads. This research is of a normative type using a statutory approach and a conceptual approach. data collection using library research techniques. The results of this research show that temporary officials have an important role in maintaining the stability and neutrality of regional elections, but their authority is limited to prevent abuse. Temporary officials are tasked with leading the government, maintaining security, facilitating regional elections, and being bound by legal and moral norms. Siyasa fiqh supports the role of temporary officials to maintain the stability and smooth running of government, with a focus on routine matters and ongoing programs. As for positive law, regulations regarding temporary acting regional heads are regulated in statutory regulations. Positive law and siyasah fiqh agree on the role of temporary officials, but differ in the institutional framework.